Genetic Underpinnings of Renal Cell Carcinoma With Leiomyomatous Stroma. (August 2019) - Parilla, Megan; Alikhan, Mir; Al-Kawaaz, Mustafa; Patil, Sushant; Kadri, Sabah; Ritterhouse, Lauren L.; Segal, Jeremy; Fitzpatrick, Carrie; Antic, Tatjana
Abstract : Renal cell carcinoma (RCC) with leiomyomatous stroma is a provisional category of RCC in the 2016 World Health Organization Classification of Tumors of the Urinary System. Microscopic examination of hematoxylin and eosin–stained sections reveals this entity to be well-circumscribed with tubulopapillary growth of cells with clear cytoplasm in a background of leiomyomatous stroma. Herein we describe the genetic features of 15 University of Chicago Medical Center archived cases with hematoxylin and eosin histology matching the provisional diagnosis. Immunohistochemical (IHC) stains revealed 1/15 of these tumors to be clear cell renal cell carcinoma (ccRCC) and 6/15 to be clear cell papillary renal cell carcinoma (ccpRCC), demonstrating the morphologic overlap with these discrete known entities. Interestingly 3/6 of the ccpRCCs had chromosome 18 gain suggesting there may be novel specific genetic changes in ccpRCC with leiomyomatous stroma. Of the remaining 8 tumors with IHC staining patterns that do not fit either ccRCC or ccpRCC only 3 of these had mutations in the recently described TCEB1 gene with concurrent monosomy of chromosome 8. These 3 cases had a somewhat unique IHC pattern that possibly could separate them from the 5 other non-ccRCC/non-ccpRCC cases. This descriptive study, although small, demonstrates the difficulty in applying the current World Health Organization provisional criteria at a single institution with suggestion of an immunohistochemcial panel that may assist in the diagnosis of TCEB1 -mutated RCC with leiomyomatous stroma.